Clinical and Cardiac Safety of Long-term Levofloxacin in Children Treated for Multidrug-resistant Tuberculosis. (16th May 2018) - Garcia-Prats, Anthony J; Draper, Heather R; Finlayson, Heather; Winckler, Jana; Burger, André; Fourie, Barend; Thee, Stephanie; Hesseling, Anneke C; Schaaf, H Simon
Abstract: Safety concerns persist for long-term pediatric fluoroquinolone use. Seventy children (median age, 2.1 years) treated with levofloxacin 10–20 mg/kg once daily for multidrug-resistant tuberculosis (median observation time, 11.8 months) had few musculoskeletal events, no levofloxacin-attributed serious adverse events, and no Fridericia-corrected QT interval >450 ms. Long-term levofloxacin was safe and well tolerated.